Immune Thrombocytopenic Purpura in Pregnancy- A Prospective Observational Study in a Tertiary Care Centre (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Objectives: Immune thrombocytopenic purpura (ITP) in pregnancy necessitates management of two patients, the mother and the newborn. Complications like maternal bleeding, fetal and neonatal thrombocytopenia demands appropriate and timely therapy. This prospective observational study was designed to explore and summarize the current approach to the investigation, diagnosis, management and outcome of ITP in pregnancy.Materials and Methods: Women with ITP admitted in the Fetomaternal Medicine Department of Bangabandhu Sheikh Mujib Medical University (BSMMU) from 2009 -2017, were included in the study. Total number of high risk pregnancy during that period were 7704 among them 20 cases were pregnancy with Immune Thrombocytopenic Purpura (ITP). Patients were managed under joint supervision of the fetomaternal medicine specialist and the hematologist. Prednisolone was considered as a first line drug in management protocol. Platelet transfusion was considered if there were symptoms or count